The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1159/000343067
|View full text |Cite
|
Sign up to set email alerts
|

The Special Programme of Research in Human Reproduction: Forty Years of Activities to Achieve Reproductive Health for All

Abstract: The Special Programme of Research in Human Reproduction (HRP), co-sponsored by the UNDP, UNFPA, WHO, and the World Bank, is celebrating 40 years of activities with an expansion of its mandate and new co-sponsors. When it began, in 1972, the main focus was on evaluating the acceptability, effectiveness, and safety of existing fertility-regulating methods, as well as developing new, improved modalities for family planning. In 1994, HRP not only made major contributions to the Plan of Action of the International … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 236 publications
0
8
0
Order By: Relevance
“…A recent report analyzing the incidence and trends of induced abortion from 1995 to 2008 worldwide, conducted by the Programme of Research in Human Reproduction and the A. Guttmacher Institute, showed that unsafe abortions have increased over time and that investments in family planning and safe abortion care are needed globally to achieve the Millennium Development Goal [16]. …”
Section: Discussionmentioning
confidence: 99%
“…A recent report analyzing the incidence and trends of induced abortion from 1995 to 2008 worldwide, conducted by the Programme of Research in Human Reproduction and the A. Guttmacher Institute, showed that unsafe abortions have increased over time and that investments in family planning and safe abortion care are needed globally to achieve the Millennium Development Goal [16]. …”
Section: Discussionmentioning
confidence: 99%
“…Lacking phones, mail services, radio, internet and television as means to transmit messages to individuals, utilizing the patient's social network to improve her chances of follow-up is clearly a tactic to be explored. Addressing such barriers to improve reproductive health for women in developing nations is a critical component of The Special Programme of Research in Human Reproduction, cosponsored by the UNDP, UNFPA, WHO, and the World Bank [8]. …”
Section: Discussionmentioning
confidence: 99%
“…The earlier studies compared three doses of LB (12.5, 25 and 50 mg) in subjects of low to normal BMI. These studies showed a clear dose response and the duration of action based on return to ovulation (12.5 mg = 105 days, 25mg = 231 days, 50mg = 265 days [2,3] with a great deal of individual variability (range) for the 25 mg dose. However, higher doses (50 mg) of the drug lasted for a much longer period (>6 months), leading to the prospect of developing a method that would last for a minimum of 4 months and possibly as long as 6 months.…”
Section: Introductionmentioning
confidence: 99%
“…However, higher doses (50 mg) of the drug lasted for a much longer period (>6 months), leading to the prospect of developing a method that would last for a minimum of 4 months and possibly as long as 6 months. Unfortunately, earlier formulations of injectable LB were found to aggregate over time, resulting in loss of product stability and reproducibility of the clinical batches [2,3]. A new formulation of LB has been developed by CONRAD (Arlington, VA) and the National Institute of Child Health and Human Development (NICHD, Bethesda, MD) that has stabilizing agents to prevent aggregation.…”
Section: Introductionmentioning
confidence: 99%